Pendampingan Masyarakat Dalam Mengidentifikasi Aspek Kesiapan Sarana Dan Prasarana Fisik Wisata Sehat Di Situ 7 Muara Tangerang Selatan - Sri Listyarini; Ulul Hidayah; Lina Warlina; Basuki Hardjodjo; Bambang Deliyant (Jurnal TUNAS, 2023)
The city of South Tangerang has nine lakes which have potential for ecotourism, one of which is Situ 7 Muara. The current condition of Situ 7 Muara does not support its development as a tourist attraction and as a healthy tourism area. Community service activities (abdimas) aim to assist the community around Situ 7 Muara in identifying the current conditions and conducting an assessment analysis of the potential of the lake as a tourist attraction, especially from the aspect of physical facilities and infrastructure that can support a healthy tourism area. The results of community service activities prove that there are five tourist points around Situ 7 Muara, namely: 1) Culinary tourism by the Situ 7 Muara lake, 2) Ganespa Educational Park, 3) Culinary tourism under the High Voltage Air Line (SUTT), 4) Urban forest, and 5) Helmet Park. From this community service activity, information was also obtained that the Information Center, accommodation, clinic/first aid, internet cafe/wartel, souvenir shop, and police/security post had poor ratings in terms of physical condition and cleanliness. As for the facilities for restaurants/restaurants, parking, garbage cans, toilets, prayer rooms, footpaths, they received good ratings in terms of their physical condition and cleanliness. Tourism development in Situ 7 Muara has not met the indicators of health tourism readiness, so that government intervention is needed.